In-vivo relation between plasma concentration of sorafenib and its safety in Chinese patients with metastatic renal cell carcinoma: a single-center clinical study - Mai, Haixing (Oncotarget, 2017)
This single-center, observational study analyzed the association between plasma concentration of sorafenib and its safety and efficacy in Chinese patients with metastatic renal cell carcinoma (mRCC). Adult patients with RCC (n = 94), treated with sorafenib were enrolled between January 2014 and January 2015. Sorafenib plasma concentrations were measured by liquid chromatography-tandem mass spectrometry. Safety and efficacy variables were evaluated using National Cancer Institute-Common Toxicity Criteria for Adverse Events and Response Evaluation Criteria in Solid Tumors criteria. Association of plasma concentration with safety and efficacy was analyzed. The steady state plasma concentration of sorafenib after 2 weeks of treatment ranged from 881 to 12,526 ng/mL. Major adverse reactions (ADRs) included diarrhea (76.5%), hand-foot syndrome (HFS; 68.99%) and fatigue (55.32%). Significant association was reported between plasma concentration and all the ADRs except rash. At 6 weeks, complete response (CR), partial response (PR), stable disease (SD) and progressive disease (PD) was reported in 3.1%, 13.82%, 52.2% and 13.82% patients, respectively. Objective response and disease control rates were 17.02% and 69.14%. Plasma concentration of sorafenib was >10,000 ng/mL in patients with severe ADRs, which decreased with reduction in dose or discontinuation of treatment. After 21.2 weeks follow-up, median progression free survival was 12.3 months. CR, PR, SD and PD were reported in 1%, 46%, 33% and 19% patients. In conclusion, plasma concentration of sorafenib was associated with its safety and efficacy in Chinese patients with mRCC.